2023
DOI: 10.1007/s11837-023-06046-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Microstructure and Local Mechanical Properties Along Build Direction for Multi-layer Friction Surfacing of Aluminum Alloys

Zina Kallien,
Marius Hoffmann,
Arne Roos
et al.

Abstract: The process variant of friction surfacing (FS) depositing multiple layers on top of each other is known as multi-layer friction surfacing (MLFS). Due to the solid-state nature of the process, re-heating is significantly reduced compared to common fusion-based AM techniques. The work gives a detailed and fundamental insight into the microstructure along the MLFS build direction for two different aluminum alloys and different process parameters. Focusing on the grain size distribution and recrystallization ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The deposited material presents almost equiaxed grains with 3.28 ± 1.83 µm. For similar process parameters and materials, Shen et al 10 reported average grain size values between 4.0 µm and 4.7 µm, which is in good agreement with Kallien et al 31 as well as the results of this study. The grain size within a MLFS stack is relatively homogeneous for every layer 10 .…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The deposited material presents almost equiaxed grains with 3.28 ± 1.83 µm. For similar process parameters and materials, Shen et al 10 reported average grain size values between 4.0 µm and 4.7 µm, which is in good agreement with Kallien et al 31 as well as the results of this study. The grain size within a MLFS stack is relatively homogeneous for every layer 10 .…”
Section: Resultssupporting
confidence: 91%
“…The consumable stud base material and MLFS deposited material did not present a difference in chemical composition for EDS analysis, but the materials are microstructurally distinct 31 , Fig. 3 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation